cAMP-stimulated Clˉ secretion is increased by glucocorticoids and inhibited by bumetanide in semicircular canal duct epithelium - Pondugula, Satyanarayana R.; Kampalli, Suresh B.; Wu, Tao; De Lisle, Robert C.; Raveendran, Nithya N.; Harbidge, Donald G.; Marcus, Daniel C. (My University, 2013)
Background: The vestibular system controls the ion composition of its luminal fluid through several epithelial cell transport mechanisms under hormonal regulation. The semicircular canal duct (SCCD) epithelium has been shown to secrete Clˉ under β2-adrenergic stimulation. In the current study, we sought to determine the ion transporters involved in Cl- secretion and whether secretion is regulated by PKA and glucocorticoids. Results: Short circuit current (I[subscript sc]) from rat SCCD epithelia demonstrated stimulation by forskolin (EC[subscript 50]: 0.8 μM), 8-Br-cAMP (EC[subscript 50]: 180 μM), 8-pCPT-cAMP (100 μM), IBMX (250 μM), and RO-20-1724 (100 μM). The PKA activator N6-BNZ-cAMP (0.1, 0.3 & 1 mM) also stimulated I[subscript sc]. Partial inhibition of stimulated I[subscript sc] individually by bumetanide (10 & 50 μM), and [(dihydroindenyl)oxy]alkanoic acid (DIOA, 100 μM) were additive and complete. Stimulated Isc was also partially inhibited by CFTR[subscript inh]-172 (5 & 30 μM), flufenamic acid (5 μM) and diphenylamine-2,2′-dicarboxylic acid (DPC; 1 mM). Native canals of CFTR+/− mice showed a stimulation of I[subscript sc] from isoproterenol and forskolin+IBMX but not in the presence of both bumetanide and DIOA, while canals from CFTR−/− mice had no responses. Nonetheless, CFTR−/− mice showed no difference from CFTR+/− mice in their ability to balance (rota-rod). Stimulated I[subscript sc] was greater after chronic incubation (24 hr) with the glucocorticoids dexamethasone (0.1 & 0.3 μM), prednisolone (0.3, 1 & 3 μM), hydrocortisone (0.01, 0.1 & 1 μM), and corticosterone (0.1 & 1 μM) and mineralocorticoid aldosterone (1 μM). Steroid action was blocked by mifepristone but not by spironolactone, indicating all the steroids activated the glucocorticoid, but not mineralocorticoid, receptor. Expression of transcripts for CFTR; for KCC1, KCC3a, KCC3b and KCC4, but not KCC2; for NKCC1 but not NKCC2 and for WNK1 but only very low WNK4 was determined. Conclusions: These results are consistent with a model of Clˉ secretion whereby Clˉ is taken up across the basolateral membrane by a Na+-K+-2Clˉ cotransporter (NKCC) and potentially another transporter, is secreted across the apical membrane via a Clˉ channel, likely CFTR, and demonstrate the regulation of Cl- secretion by protein kinase A and glucocorticoids.
Keywords: Chloride secretion; Rat; Knockout mouse; Primary culture; Epithelium; Inner ear; Bumetanide; DIOA; Glucocorticoid; NKCC; KCC